ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LINGKUNGAN INDONESIA - Annisa Fatmawati; Dedy Yuliawan; Zulfa Emalia; Irma Febriana MK (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
This study investigates the impact of key factors, Industrial Regional Gross Domestic Product (PDRB), population density, deforestation, and waste generation, on the Environmental Quality Index (IKLH) in Indonesia. The primary objective is to understand how these variables affect environmental quality across different regions. Using a panel data regression approach covering the years 2019-2023, this research employs various statistical tests, including Chow, Hausman, and Lagrange Multiplier tests, to know the appropriate model (FEM). The results indicate that PDRB sector industry and population density positively influence the IKLH, suggesting that industrial growth and effective population management can contribute to improved environmental quality. In contrast, deforestation negatively affects the IKLH, highlighting the detrimental impact of deforestation on ecosystem services such as carbon absorption and biodiversity. Although waste generation shows a positive effect, it is not statistically significant, indicating that waste management practices play a crucial role in mitigating environmental degradation. The study concludes that sustainable industrial development, effective population control, deforestation management, and robust waste management systems are key to enhancing Indonesia’s environmental quality.